Analisis Kualitas Layanan terhadap Kepatuhan Masyarakat Membayar Pajak Kendaraan dan Peningkatan Penerimaan Pajak Kendaraan Bermotor - Hendrik Kristian (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This research was conducted with the intent and purpose to test the significance of service quality to public compliance in paying vehicle taxes at the Kantor Bersama Samsat Kediri Kota; Test the significance of service quality towards increasing motor vehicle tax revenue in the Joint Office of Samsat Kediri City; Test the significance of community compliance in paying motor vehicle tax to increase motor vehicle tax revenue at the Joint Office of Samsat Kediri City. The study will be conducted at the Joint Office of Samsata Kediri City with a total sample of 344 taxpayers who own four-wheeled vehicles. The research data was taken using an instrument in the form of a questionnaire, the data collected will be analyzed using a regression test to see the relationship between the research variables studied. The results of this study have the following conclusions; There is a positive and significant effect on the quality of service on public compliance paying motor vehicle tax at the Joint Office of Samsat Kediri City; There is a positive and significant effect on the quality of service on increasing motor vehicle tax revenue in the Joint Office of Samsat Kediri City; There is a positive and significant effect of public compliance in paying motor vehicle tax to increase motor vehicle tax revenue at the Joint Office of Samsat Kediri City.